Scientific Basis for Eccentric Quasi-Isometric Resistance Training: A Narrative Review. Issue 10 (October 2019) - Oranchuk, Dustin J.; Storey, Adam G.; Nelson, André R.; Cronin, John B.
Abstract : Abstract: Oranchuk, DJ, Storey, AG, Nelson, AR, and Cronin, JB. The scientific basis for eccentric quasi-isometric resistance training: A narrative review. J Strength Cond Res 33(10): 2846–2859, 2019—Eccentric quasi-isometric (EQI) resistance training involves holding a submaximal, yielding isometric contraction until fatigue causes muscle lengthening and then maximally resisting through a range of motion. Practitioners contend that EQI contractions are a powerful tool for the development of several physical qualities important to health and sports performance. In addition, several sports involve regular quasi-isometric contractions for optimal performance. Therefore, the primary objective of this review was to synthesize and critically analyze relevant biological, physiological, and biomechanical research and develop a rationale for the value of EQI training. In addition, this review offers potential practical applications and highlights future areas of research. Although there is a paucity of research investigating EQIs, the literature on responses to traditional contraction types is vast. Based on the relevant literature, EQIs may provide a practical means of increasing total volume, metabolite build-up, and hormonal signaling factors while safely enduring large quantities of mechanical tension with low levels of peak torque. Conversely, EQI contractions likely hold little neuromuscular specificity to high velocity or power movements. Therefore, EQI training seems to be effective for improving musculotendinous morphological and performance variables with low injury risk. Although speculative due to the limited specific literature, available evidence suggests a case for future experimentation.